Spatiotemporally and Mechanically Controlled Triggering of Mast Cells using Atomic Force Microscopy - Hu, Kenneth K. (2014)
Mast cells are thought to be sensitive to mechanical forces, for example, coughing in asthma or pressure in “physical urticarias”. Conversion of mechanical forces to biochemical signals could potentially augment antigenic signaling. Studying the combined effects of mechanical and antigenic cues on mast cells and other hematopoietic cells has been elusive. Here, we present an approach using a modified atomic force microscope cantilever to deliver antigenic signals to mast cells while simultaneously applying mechanical forces. We developed a strategy to concurrently record degranulation events by fluorescence microscopy during antigenic triggering. Finally, we also measured the mechanical forces generated by mast cells while antigen receptors are ligated. We showed that mast cells respond to antigen delivered by the AFM cantilever with prompt degranulation and the generation of strong pushing and pulling forces. We did not discern any relationship between applied mechanical forces and the kinetics of degranulation. These experiments present a new method for dissecting the interactions of mechanical and biochemical cues in signaling responses of immune cells.